RESPON MASYARAKAT TERHADAP PENERAPAN UNDANG-UNDANG NOMOR 22 TAHUN 2009 PASAL 107 AYAT 2 TENTANG MENYALAKAN LAMPU UTAMA DI SIANG HARI (LIGHT ON) BAGI PENGENDARA SEPEDA MOTOR (Studi Kasus di Kelurahan Labuhan Ratu Kecamatan Kedaton Kota Bandar Lampung) - Sistira, Wera Auliag; Suwarno, Suwarno (SOCIOLOGIE, 2013)
This study aims to identify and explain how the public response to the application of Law No. 22 of 2009 Section 107 Paragraph 2 of the Main Lamp Lit Day For Motorcycle Riders in the Village District of Aston Tropicana Labuhan Ratu Bandar Lampung, this study used a descriptive research method using data collection techniques, the questionnaire distributed to respondents using accidental sampling technique domiciled in Labuan Ratu Village District of Aston Tropicana Bandar Lampung. Selection of communities in the region because of social phenomena which occur very dynamic, especially concerning the application of rules in driving the light on, meaning that peoples behavior patterns in the region in the application of rules in driving not much different. So the researchers took a sample of 30 people motor.Teknik bike users using a single table of data analysis, a method that is done by entering the data from the questionnaire within the framework of the table to calculate the frequency and make a percentage. The results of this study were 12 respondents (40%) gave a positive response or agree with the implementation of Law No. 22 of 2009 Section 107 Paragraph 2 of the headlights turned on during the day for motorcyclists and 18 respondents (60%) gave a negative response or no agree to the application of Law No. 22 of 2009 Section 107 Paragraph 2 of the headlights turned on during the day for the bikers.Keywords: Public response, light on, motorcycle riders